A reliable method for the isolation and characterization of microplastics in fish gastrointestinal tracts using an infrared tunable quantum cascade laser system. (May 2022) - López-Rosales, Adrián; Andrade, Jose; Fernández-González, Verónica; López-Mahía, Purificación; Muniategui-Lorenzo, Soledad
Abstract: Societal and environmental concern due to frequent reports of microplastics in fish stomachs raised as they may accumulate along the trophic chain. The request for analysing microplastics in fish stresses two major analytical issues: sample treatment and final characterization. The, so far, workhorse for chemical characterization is infrared spectroscopy which is time-consuming. Here, a quantum cascade laser-based device is used to accelerate the characterization stage. Its novelty poses new challenges for sample processing and particle handling because the unknown particles must be transferred to a reflective slide . In this study, three sample digestion protocols (alkaline-oxidative with H2 O2, and alkaline-oxidative with NaClO and enzymatic-oxidative) and three different procedures to transfer the filter cake to reflective slides are compared. A simplified enzymatic-oxidative digestion (validated through an interlaboratory exercise) combined with a Syncore® automatic evaporation system and a Laser Direct Infrared Imaging (LDIR) device is proposed first time as a reliable and relatively fast method to treat gastrointestinal tracts of fish. Analytical recoveries were studied using samples of Scomber scombrus and they were ca. 100% for big –i.e., >500 μm- and ca. 90% for medium –i.e., 200–300 μm- particles and ca. 75% for 10 μm thick fibres. Graphical abstract: Unlabelled Image Highlights: Three digestion methods for gastrointestinal tract digestion were studied. Enzymatic-oxidative digestion plus H2 O2 bleaching yielded excellent recoveries. Three forms of particle transfer to LDIR reflective slides were studied. Manual pickup and total filtrate transfer led ≥90% recoveries for ≥10 μm. The method allowed satisfactory recoveries of fibres, ca. 75%.